Analisis Perbandingan Undang-Undang Nomor 1 Tahun 1974 Tentang Perkawinan dan Kompilasi Hukum Islam dalam Perspektif Cacat Badan sebagai Alasan Perceraian" - Yainahu, Mirsa (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to analyze the regulation of physical disability as grounds for divorce in Law No. 1 of 1974 and the Compilation of Islamic Law (KHI), as well as the implications of these legal provisions on the protection of individual rights in the divorce process. The research findings indicate that although both regulations recognize physical disability as a legitimate reason for divorce, there are differences in the approach to regulating and protecting the rights of the parties involved. Law No. 1 of 1974 focuses more on formal legal procedures and proof of divorce grounds, while KHI gives more attention to the protection of women's and children's rights, such as iddah maintenance, mut’ah, and child custody. The implications of these regulations highlight the need for harmonization between positive law and Islamic law to ensure justice and protection of the rights of spouses in divorce. The recommendations include strengthening proof standards, protecting women's and children's rights, and integrating moral and social values into divorce-related legal provisions.